Fracture Characteristics and Reservoir Inhomogeneity Prediction of the Gaoyuzhuang Formation in the Xiong’an New Area: Insights From a 3D Discrete Fracture Network Model - Yue, Gaofan; Wang, Guiling; Ma, Feng; Zhu, Xi; Zhang, Hanxiong; Zhou, Jianwei; Na, Jin (Frontiers in Earth Science, 2022)
The Xiong'an new area in northern China is rich in geothermal resources. The Gaoyuzhuang Formation in the Proterozoic Jixian system is an important recently discovered geothermal reservoir. The Gaoyuzhuang reservoir has been affected by multiple stages of tectonic movement. The fractures are very well developed, resulting in strong heterogeneity in the reservoir’s porosity and permeability. Few studies have been conducted on the fractures and heterogeneity of the Gaoyuzhuang reservoir. In this study, interpretation of data from image logs was used to summarize the characteristics of the fractures, including the fractures’ strikes, dips, and lengths. The permeability distribution of the reservoir in the vicinity of the borehole was predicted. The hydro-thermal (TH) coupling model was used to reproduce the process of pumping tests, and the simulation results were found to be in good agreement with the field test data. In addition, the relationship between the fracture aperture and length was obtained, d_max=4.2×〖10〗^(-5)∙L^0.5. The results of this study provide data and technical support for further reservoir research and evaluation of the geothermal resources of the Gaoyuzhuang reservoir.